A family of Analytic Functions Subordinate to Horadam Polynomials (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce and investigate a family of analytic functions, denoted by $\mathcal{F}(Π, α, β, λ, δ, μ)$, defined by means of Horadam polynomials. For functions in this family, we derive the estimations for the initial Taylor-Maclaurin coefficients $|a_2|$ and $|a_3|$. Moreover, we obtain the classical Fekete-Szegö inequality of functions belonging to this family.
Keywords: Analytic Functions; Taylor-Maclaurin Series; Principle of Subordination; Horadam Polynomials; Chebyshev polynomials; Coefficient estimates; Fekete-Szeg\